Occurrence of Atopozelus opsimus preying on nymphs and adults of Glycaspis brimblecombei - Ribeiro Dias, Thaise Karla [UNESP]; Wilcken, Carlos Frederico [UNESP]; Soliman, Everton Pires [UNESP]; Gil-Santana, Helcio R.; Zache, Bruno [UNESP] (Springer, 2012)
The stink bugs genus Atopozelus (Hemiptera: Reduviidae) is native in the Americas, with five described species of which only three have been recorded in Brazil. In August 2007, Eucalyptus camaldulensis leaves infested by lerp psyllid were collected and taken to the Forest Pest Biological Control Laboratory situated at São Paulo State University. A small green stink bug, identified as Atopozelus opsimus Elkins (Hemiptera: Reduviidae) that fed on nymphs and adult psyllids, was found on the leaves. These stink bugs presented phytophagy, omnivory and ability in opening the lerp (shell) that protect the psyllid. A. opsimus has demonstrated unusual particularities, different from many biological control agents found in nature; this predator thus deserves more attention for its potential to be evaluated.
Keywords: Biological control; Eucalyptus; Lerp psyllids; Predator; Stink bugs